Assessment of the Characters of a Novel Phosphoric Acid and Mineral-Comodified Biochar Composite and Its Potential Application in Saline–Alkali Soil Improvement - Hao Dai; Zhuangzhuang Liu; Jinping Yu; Xiaoming Teng; Lei Liu; Mingyun Jia; Jianhui Xue (Agriculture)
Amending saline–alkali soils to improve agricultural productivity is critical for addressing global food security challenges. Biochar is a promising soil amendment, and its modified composites offer significant potential for soil remediation. In this study, we developed a novel phosphoric acid–mineral-comodified biochar composite for saline–alkali soil improvement. SEM and XRD analyses indicate that chemical interactions between phosphoric acid, minerals, and biochar result in the formation of distinct mineral phases on the composite surface. Furthermore, FTIR analysis reveals that these interactions give rise to functional groups such as Si-O-Si, and thermogravimetric analysis demonstrates that the modified biochar composite exhibited enhanced stability. Compared with raw biochar, the modified biochar composites exhibited significant decreases in pH, EC, and base cation content (especially Na+), with maximum reductions of 7.26 pH units, 639.5 μS/cm, and 3.69 g/kg, respectively. In contrast, the contents of P, Si, and Ca increased significantly, with maximum increases of 140.04 g/kg, 90.32 g/kg, and 114.27 g/kg, respectively. In addition, the specific surface area and pore volume of the modified biochar composite increased by up to 5.2 and 15 times, respectively. Principal component analysis indicates that mineral type was the primary factor influencing the properties of the composites: hydroxyapatite enhanced porosity and phosphorus levels, whereas kaolinite and montmorillonite increased silicon content. Pot experiments show that the modified biochar composite increased alfalfa plant height by 17.36–20.27% and shoot biomass by 107.32–125.80% in saline–alkali soils. Overall, the newly developed phosphoric acid–mineral–biochar composites were evaluated to have high application potential for saline–alkali soil amendment.